2021
DOI: 10.1016/j.ejvs.2020.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Celiprolol Treatment in Patients with Vascular Ehlers-Danlos Syndrome

Abstract: WHAT THIS PAPER ADDS The French/Belgian Beta blockers in Ehlers-Danlos Syndrome Treatment (BBEST) trial reported in 2010 that the number of serious/fatal vascular events could be halved by treating patients with vascular Ehlers-Danlos syndrome with celiprolol. Prior to that publication, no evidence based treatment could be offered to patients or their relatives carrying the same pathogenic variant of the procollagen 3A1 gene. This disease is rare, explaining why this is the second largest cohort published on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 25 publications
2
30
1
4
Order By: Relevance
“…Patients suffering from vEDS have a life expectancy mainly reduced by the occurrence of unpredictable arterial rupture in young adulthood. Despite randomized open clinical trial [ 10 ] and cohorts surveys [ 11 , 27 ] data, there is no consensus on a continuous medical therapy that could prevent that risk [ 2 , 28 ]. In such a rare disease, the development of pre-clinical models is particularly useful to test different therapies and better understand the consequences of the disease at the cellular and tissue levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients suffering from vEDS have a life expectancy mainly reduced by the occurrence of unpredictable arterial rupture in young adulthood. Despite randomized open clinical trial [ 10 ] and cohorts surveys [ 11 , 27 ] data, there is no consensus on a continuous medical therapy that could prevent that risk [ 2 , 28 ]. In such a rare disease, the development of pre-clinical models is particularly useful to test different therapies and better understand the consequences of the disease at the cellular and tissue levels.…”
Section: Discussionmentioning
confidence: 99%
“…In vEDS, only celiprolol has been rigorously tested [37] showing a significant benefit on cardiovascular mortality and morbidity on a limited number of molecularly-proven patients [10]. Its good tolerance and beneficial effects were also shown in a French cohort with long-term survey (9 years) [11], and a 2-year follow-up of 40 Swedish patients [27]. The significance of these results being disputed, we tested both propranolol, the oldest non-selective βblocker generally used in experimental studies, and celiprolol (at therapeutic plasma concentration).…”
Section: Plos Geneticsmentioning
confidence: 99%
“…There is no established medical treatment in vEDS, but studies have suggested that treatment with celiprolol, a cardioselective β1 blocker with a vasodilatory effect, may reduce the frequency of arterial events. 5 The patient had no relatives with known vEDS, but approximately 50% of all patients have a de novo mutation, making it possible that she was the first in her family with vEDS.…”
Section: Discussionmentioning
confidence: 99%
“…Patients suffering from vEDS have a life expectancy mainly reduced by the occurrence of unpredictable arterial rupture in young adulthood. Despite randomized open clinical trial (9) and cohorts surveys (11,27) data, there is no consensus on a continuous medical therapy that could prevent that risk (2) (28). In such a rare disease, the development of pre-clinical models is particularly useful to test different therapies and better understand the consequences of the disease at the cellular and tissue levels.…”
Section: Discussionmentioning
confidence: 99%
“…Its good tolerance and beneficial effects were also shown in a French cohort with long-term survey (9 years) (10), and a 2-year follow-up of 40 Swedish patients. (27) The significance of these results being disputed, we tested both propranolol, the oldest non-selective β-blocker generally used in experimental studies, and celiprolol (at therapeutic plasma concentration). Both β-blockers had no beneficial effect on Col3a1 +/G182R mice survival.…”
Section: Discussionmentioning
confidence: 99%